2021
DOI: 10.1109/tro.2020.3046415
|View full text |Cite
|
Sign up to set email alerts
|

Representation-Free Model Predictive Control for Dynamic Motions in Quadrupeds

Abstract: This paper presents a novel Representation-Free Model Predictive Control (RF-MPC) framework for controlling various dynamic motions of a quadrupedal robot in three dimensional (3D) space. Our formulation directly represents the rotational dynamics using the rotation matrix, which liberates us from the issues associated with the use of Euler angles and quaternion as the orientation representations. With a variationbased linearization scheme and a carefully constructed cost function, the MPC control law is trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 63 publications
0
47
0
Order By: Relevance
“…The existing control approaches for quadrupedal locomotion rely on accurately estimated state input [1], [3], [4], [7], [10]- [13]. However, we observed that existing This work was supported by Samsung Research Funding & Incubation Center for Future Technology at Samsung Electronics under Project Number SRFC-IT2002-02.…”
Section: Introductionmentioning
confidence: 99%
“…The existing control approaches for quadrupedal locomotion rely on accurately estimated state input [1], [3], [4], [7], [10]- [13]. However, we observed that existing This work was supported by Samsung Research Funding & Incubation Center for Future Technology at Samsung Electronics under Project Number SRFC-IT2002-02.…”
Section: Introductionmentioning
confidence: 99%
“…2) Gait Synthesis and Characterization: The 3D composition of planar orbits offers a way of synthesizing and characterizing 3D bipedal walking gaits. The gait synthesis and characterization via composition of planar orbits can potentially be extended to other multi-legged systems, e.g., the bounding behavior on quadrupedal locomotion [59] can be viewed as producing a P2 orbit in its sagittal plane. The extension appears to be non-trivial but possible.…”
Section: A Implicationsmentioning
confidence: 99%
“…Building upon similar ideas, regularized predictive control frameworks that addresses nonlinearities in the original problem via convexifying the cost function have been designed and verified with hardware implementations [26][27][28]. Leveraging a variational-based linearization technique, optimization-based strategies have demonstrated their ability to manage underactuated balance [29] and dynamic locomotion [30]. Winkler et al [31] worked directly with the nonlinear problem and applied standard solvers to tackle the problem.…”
Section: Related Workmentioning
confidence: 99%